2k + 4 + 2k = -6 + 3
4k + 4 = -3
4k = -7
k = -7 / 4
2006-11-24 06:49:12
·
answer #1
·
answered by Jen 2
·
0⤊
0⤋
2k + 4 + 2k = -6 + 3 combine like terms
4k+4=-3 subtract 4
4k=-7 divide by 4
k=-7/4
2006-11-24 14:33:14
·
answer #2
·
answered by yupchagee 7
·
0⤊
0⤋
2k+2k = -6+3-4
4k = -7
k = -7/4
2006-11-24 13:41:49
·
answer #3
·
answered by azka a 2
·
1⤊
0⤋
2k + 4 + 2lk = - 6 + 3
4k + 4 = - 3
4k + 4 - 4 = - 3 - 4
4k = - 7
4k/4 = -7/4
k = - 7/4
k = 1 3/4
k= 1.75
The answer is k = 1.75
- - - - -s-
2006-11-24 14:59:03
·
answer #4
·
answered by SAMUEL D 7
·
0⤊
1⤋
k.(2+2)=-6+3-4
4.k=-7 then k = -7/4 ( the correct answer)
2006-11-24 14:55:45
·
answer #5
·
answered by cgds_81 1
·
0⤊
0⤋
The first answer is correct.
k= -7/4
2006-11-24 13:44:17
·
answer #6
·
answered by Ozz 5
·
0⤊
0⤋
If you're asking to solve for k, then:
k = -7/4
2006-11-24 13:41:01
·
answer #7
·
answered by Anonymous 7
·
1⤊
0⤋
step:1 4k+4= -3
step:2 4k= -3-4
step:3 4k=-7
step;4 k= -7/4 (this is answer)
2006-11-24 15:40:46
·
answer #8
·
answered by love88 2
·
1⤊
0⤋
4k + 4 = -3
k = -7/4
2006-11-24 13:35:15
·
answer #9
·
answered by Anonymous
·
1⤊
1⤋
4k=-7
k= -7/4
2006-11-24 13:37:43
·
answer #10
·
answered by Anonymous
·
1⤊
0⤋